Who Opts Out of the Statutory Health Insurance? A Discrete Time Hazard Model for Germany - Christian Bünnings; Harald Tauchmann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
The coexistence of social health insurance and private health insurance in Germany is subject to intense public debate. As only few have the opportunity to choose between the two systems, they are often regarded as privileged by the health insurance system. Applying a hazard model in discrete time, this paper examines the role of incentives set by the regulatory framework as well as the influence of individual personality characteristics on the decision to opt out of the statutory system. To address potential endogeneity of one of the key explanatory variables an instrumental variable approach is also applied. The estimation results yield robust evidence on the choice of health insurance type that is consistent with rational decision making, with both incentives set by regulation and personality traits as relevant determinants. – – Die Koexistenz von gesetzlicher und privater Krankenversicherung in Deutschland ist Gegenstand intensiver öffentlicher Debatten. Da lediglich eine Minderheit der Versicherten die Wahl zwischen beiden Systemen hat, wird diese Minderheit oft als privilegiert betrachtet. Auf Basis des Sozioökonomischen Panels (SOEP) und unter Verwendung eines Hazard-Models in diskreter Zeit untersucht dieses Papier die Wirkung von Anreizen, die sich aus den gesetzlichen Rahmenbedingungen ergeben sowie den Einfluss von individuellen Persönlichkeitsmerkmalen auf das Wechselverhalten. Um die potenzielle Endogenität des Gesundheitszustandes zu berücksichtigen, wird außerdem ein Instrumenten-Variablen Ansatz verwendet. Die empirischen Ergebnisse liefern robuste Evidenz, dass die Wahl des Krankenversicherungssystems konsistent mit rationalem Entscheidungsverhalten ist und sowohl durch gesetzliche Anreize als auch durch individuelle Persönlichkeitsmerkmale determiniert ist.
Keywords: C13; C23; I13; 330; statutory and private health insurance; incentives; personality traits